Ménage-à-trois: the amoeba Nuclearia sp. from Lake Zurich with its ecto- and endosymbiotic bacteria - Dirren, Sebastian; Salcher, Michaela M; Blom, Judith F; Schweikert, Michael; Posch, Thomas (Protist, 2014)
We present a fascinating triad relationship between a eukaryotic amoeba and its two bacterial symbionts. The morphological characteristics of the amoeba allowed for a confident assignment to the genus Nuclearia (Opisthokonta, Nucleariidae), but species identification resulted in an ambiguous result. Sequence analysis indicated an affiliation to the species N. thermophila, however, several morphological features contradict the original description. Amoebal isolates were cultured for several years with their preferred food source, the microcystin-producing harmful cyanobacterium Planktothrix rubescens. Symbioses of the amoeba with ecto- and endosymbiotic bacteria were maintained over this period. Several thousand cells of the ectosymbiont are regularly arranged inside a layer of extracellular polymeric substances produced by the amoeba. The ectosymbiont was identified as Paucibacter toxinivorans (Betaproteobacteria), which was originally isolated by enrichment with microcystins. We found indications that our isolated ectosymbiont indeed contributed to toxin-degradation. The endosymbiont (Gammaproteobacteria, 15-20 bacteria per amoeba) is enclosed in symbiosomes inside the host cytoplasm and represents probably an obligate symbiont. We propose the name "Candidatus Endonucleariobacter rarus" for this bacterium that was neither found free-living nor in a symbiotic association. Nucleariidae are uniquely suited model organisms to study the basic principles of symbioses between opisthokonts and prokaryotes.
Keywords: symbióza; Amoeba; protozoální DNA; Švýcarsko; RNA, Ribosomal, 18S; RNA, Ribosomal, 16S; Betaproteobacteria; Lakes; Sequence Analysis, DNA; ectosymbionts; ribozomální DNA; sekvenční analýza DNA; molekulární sekvence - údaje; endosymbionts; DNA, Protozoan; mezerníky ribozomální DNA; jezera; RNA, Protozoan; geny rRNA; DNA, Bacterial; DNA bakterií; Genes, rRNA; Switzerland; Paucibacter toxinivorans.; Nucleariidae; RNA protozoální; RNA ribozomální 16S; DNA, Ribosomal Spacer; Molecular Sequence Data; feeding; Symbiosis; DNA, Ribosomal; RNA ribozomální 18S; Bacteria-protist symbioses; Gammaproteobacteria